ANALISIS FAKTOR KETERLAMBATAN PELAKSANAAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH KOTA PEKANBARU TAHUN 2010-2012 - Pratama, Oksi Mari; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study wanted to see how the implementation of the Regional Budget (APBD) Pekanbaru City 2010-2012. The problem is the background of this research is how the implementation of the budget data Pekanbaru City in 2010-2012 and what factors inhibiting the implementation of Pekanbaru City budget years 2010-2012? This study is a qualitative research, the data collection techniques in this research is descriptive analysis. This research uses documentation (observation) and interview with key informants as an object of information that aims to achieve the goal in order to obtain the information in the study. Data used in this study are primary data and secondary data obtained through direct observation and interviews with key informants in this study. Based on the analysis in the previous chapter, it can be concluded that a few years back that cause delays implementation Belaja Regional Budget (APBD) Pekanbaru City caused by the delay in Pekanbaru City Government handed over the dossier in the draft budget to the Regional Representatives Council (DPRD) Pekanbaru City mberdampak to thes time for discussion of the proposed budget that it shall normatively been disbursed in mid January may be delayed several months. Keywords; Policy, Budget, Interests